2021
DOI: 10.1016/j.neurobiolaging.2021.02.018
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 p.M1646T is associated with glucocerebrosidase activity and with Parkinson's disease

Abstract: Background and objectives: The LRRK2 p.G2019S Parkinson's disease (PD) variant is associated with elevated glucocerebrosidase (GCase) activity in peripheral blood. We aimed to evaluate the association of other LRRK2 variants with PD and its association with GCase activity.Methods: LRRK2 and GBA were fully sequenced in 1,123 PD patients and 576 controls from the Columbia and PPMI cohorts, in which GCase activity was measured in dried blood spots by liquid chromatography-tandem mass spectrometry. Results: LRRK2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Second, methodological differences in the assessment of GCase activity (i.e., cell based vs. in vitro) may capture different aspects of this interplay. A further study on blood samples from PD-patients identified a correlation between the LRRK2 variant M1646T and increased GCase activity 17 , consistent with the result we had obtained for LRRK2 G2019S carriers 14 .…”
Section: Introductionsupporting
confidence: 89%
“…Second, methodological differences in the assessment of GCase activity (i.e., cell based vs. in vitro) may capture different aspects of this interplay. A further study on blood samples from PD-patients identified a correlation between the LRRK2 variant M1646T and increased GCase activity 17 , consistent with the result we had obtained for LRRK2 G2019S carriers 14 .…”
Section: Introductionsupporting
confidence: 89%
“…Both cohorts have been previously described in detail. 14 , 21 , 22 Rare variants analysis was performed in three cohorts sequenced at McGill University from Columbia University, McGill University (Quebec, Canada and Montpellier, France) and Sheba Medical Center ( Table 1 ). In addition, rare variants analysis was performed in the Accelerating Medicines Partnership-Parkinson Disease (AMP-PD) initiative cohorts ( https://amp-pd.org/ ).…”
Section: Methodsmentioning
confidence: 99%
“…The Columbia University cohort (New York) and the Parkinson’s Progression Markers Initiative (PPMI) cohort (detailed in Table 1). Both cohorts have been previously described in detail 14,21,22 . Rare variants analysis was performed in three cohorts sequenced at McGill university from Columbia University, McGill University (Quebec, Canada and Montpellier, France) and Sheba Medical Center (Table 1).…”
Section: Methodsmentioning
confidence: 99%